The Body, Broken for You. Herman Nitsch and the Building of Community - Parent, Vanessa (IKON, 2015)
Abstract The following study examines the use of Christian iconography present in Hermann Nitsch’s Orgies Mysteries Theatre project in relation to the problematics of Community. I situate my inquiry within the geopolitical and historical specificity of post-war Austria, more specifically in relation to mass secularization and to the alienation from communal existence experienced within late-capitalist climate of the post-war period. I argue for an understanding of Nitsch’s radical inclusion of the body and transgressive use of Christian visual language as an attempt to create a true experience of community, what philosopher Jean-Luc Nancy would characterize as a “being-in-common”, at the moment of performance. Abstract Ova studija raspravlja o korištenju kršćanske ikonografije u Teatru orgija i misterija, Hermanna Nitscha (Orgies Mysteries Theater - OMT), u odnosu prema problematizaciji zajednice. Autorica smješta svoje istraživanje unutar specifičnoga geo-političkog i povijesnog okvira poslijeratne Austrije, preciznije - u odnos s pojavom masovne sekularizacije i alijenacije unutar zajednice, što se odvija pod utjecajem kasnokapitalističkog duha u poslijeratnom periodu. Parent se zalaže za razumijevanje i prihvaćanje Nitchove radikalne inkluzije tijela i transgresivne upotrebe kršćanskog vizualnog jezika u pokušaju kreiranja istinskog doživljaja zajednice, onoga što bi filozof Jean-Luc Nancy odredio kao bitak-u-zajedništvu, u trenutku izvedbe (performansa).